PERCEPTION OF QUALITY OF WORK LIFE AMONG TEACHERS IN A PUBLIC SCHOOL (CIPEEX, 2024)
According to the World Health Organization (WHO), health is related to physical, mental, and social well-being, and not merely the absence of disease. Health is not just the absence of illnesses but is also intrinsically linked to our psychological well-being. The perspective of health and work is related to the health of teachers because work overload is associated with everyday tensions and affects their mental health, as it is related to anxiety, insomnia, and muscle tension (body pain). This overload is connected to the difficulties faced due to the variabilities associated with work. The objective of this study was to understand the Quality of Work Life (QWL) of teachers in a school in the city of Ipiranga-GO. The Walton QWL questionnaire was used as a research instrument and was administered in person to 21 teachers of both sexes. The results revealed that most participants consider their QWL to be moderate. This result suggests that, although teachers do not face extremely adverse conditions, they also do not experience an ideal work environment. The "moderate" classification points to the presence of factors that both contribute to and hinder well-being in the workplace. Regarding working conditions, teachers may face challenges related to inadequate infrastructure or a lack of pedagogical resources, despite having reasonable physical conditions. On the other hand, work overload may limit opportunities for professional development and full use of teachers' capacities. In terms of growth and job security, a lack of recognition and opportunities for career advancement can negatively impact teachers' perception of job security. Regarding social integration at work, although there may be reasonable interpersonal relationships, communication problems and the absence of a positive organizational culture can negatively affect the work environment. Furthermore, there may be a feeling of a lack of respect for individual rights in the school environment, leading to a moderate perception of organizational justice. It is concluded that, although the QWL of teachers in Ipiranga-GO is considered moderate, there is significant room for improvement. A multifaceted approach that addresses both working conditions and psychological support and professional development will be essential to improving teachers' QWL and, consequently, the quality of education provided.
Keywords: quality of work life; teachers; walton model